Persepsi Kesenjangan Sosial dan Ekonomi di Indonesia Melalui Spekulatif Desain - Alvaro, Tristan Fawwaz; Hairunnas, Hairunnas; Hartanto, Kenny (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2025)
Exploring speculative design’s potential as a critical medium for raising Indonesian public awareness of social and economic inequalities, this study tests three approaches: What‑Ifs, Counterfactual, and Reductio ad Absurdum, within the Cone of Plausibility framework. Methodology combined field observation, Focus Group Discussions (FGDs) with university students and middle‑class workers (n = 8–12), thematic analysis, and sentiment scoring. Results show that What‑Ifs generated enthusiasm for sustainable innovation but raised concerns about affordability and cultural impact; Counterfactual stimulated intellectual reflection yet was often seen as insufficiently relevant locally; and Reductio ad Absurdum elicited strong emotional responses by highlighting systemic injustices but required clear action pathways to avoid mere provocation. These findings suggest that speculative design can effectively foster critical dialogue when grounded in local context and supported by implementation recommendations. The study provides a methodological framework and comparative analysis that can guide designers and policymakers in creating design‑based social interventions.